Weaning Alters Intestinal Gene Expression Involved in Nutrient Metabolism by Shaping Gut Microbiota in Pigs - Meng, Qingwei; Luo, Zhang; Cao, Chunyu; Sun, Shishuai; Ma, Qingquan; Li, Zhongyu; Shi, Baoming; Shan, Anshan (Frontiers in Microbiology, 2020)
Weaning transition usually impairs intestinal architecture and functions and results in gut-associated disorders in pigs. Understanding the changes in intestinal transcriptome and gut microbiota during weaning transition is important for elucidating the underlying mechanism of weaning stress. In the present study, we performed RNA-seq to determine the changes in intestinal transcriptome and 16S rRNA sequencing to measure the gut microbiota changes in the weaning transition. Transcriptome results indicated that weaning transition altered intestinal gene expression involved in nutrient transport and metabolism. Regarding fatty metabolism, fatty acid-binding protein 1 (FABP1), acyl-CoA dehydrogenase (ACADSB) and carnitine palmitoyltransferase 2 (CPT2) expression in the intestine was decreased by weaning. Genes related to bile acid metabolism were increased by weaning, including FABP6, farnesoid X receptor (FXR or NR1H4) and organic solute transporter-α (SLC51A). In addition, genes associated with oxidative stress were altered by weaning transition, including decreased catalase (CAT) and lactate dehydrogenase (LDHA) and increased glutathione peroxidase 2 (GPX2) and superoxide dismutase 3 (SOD3). Results of microbiota composition showed that the Firmicutes abundance and Firmicutes/ Bacteroidetes ratio were increased and that the Proteobacteria abundance in the fecal microbiota was decreased by the weaning process; during the weaning transition, the Bacteroides and Fusobacterium abundances decreased markedly, and these bacteria nearly disappeared, while the Prevotella abundance showed a marked increase. Moreover, the levels of the microbial metabolites butyrate and acetate increased with changes in gut microbiota composition. In addition, predictive metagenome by PICRUSt analysis showed that the pathways related to D-glutamine and D-glutamate metabolism, citrate cycle (TCA cycle), PPAR signaling, alpha-linolenic acid metabolism were decreased and the pathway related to retinol metabolism was increased in the gut microbiota of piglets during weaning transition. Our results showed that early weaning alters intestinal gene expression involved in nutrient metabolism, which may be due to the changes in microbiota composition.